A bruxa nos contos de fadas - Trindade, Nancy Rabello de Barros (2008)
This paper´s objective is to focus on the witch of the fairy tales - more specifically on they way witches are perceived by adults and children. In order to better understand and develop this theme, it seeks background on Jung himself and authors as Paz, von Franz, Coelho, Byington - who follow the Analytical Psychology of Jung on their studies about fairy tales. The research is enriched by the perspectives of authors as Darnton, Clark and Nogueira, who analyze the construction of the images of the witch and the woman within the historical context. The structure of the fairy tale was based on Propp's view among other authors who analyze the fairytale through the actions of the characters within it. It was also analyzed the contribution of this character to the development of the children's personality. The main concepts related to fairy tales (archetypes, Great Mother and other archetypical images) were also identified on several chapters. The symbols and images are the focus of the following chapter, as it is through the symbolic language that the fairy tales bring out their meanings to the mankind. The authors used to understand the symbols are Byington, Neumann, Bussato and Kast among others. This study is divided in 2 great moments: theoretic data and interviews conduct among children and adults. For interviews work, 3 stories were chosen: Hänsel and Grethel, Snow white and Rapunzel, which represent the witch in 3 different perspectives. After listening to the stories, the children were invited to draw the witch. Those drawings were analyzed using as a starting point the theories of Arttherapy, supported by authors as Futh, Derdyk, Cox and Mèredieu. The conclusion achieved from the conducted study is that the witches are not perceived by children as being totally mean, and that this character has a fundamental part in order to allow the fairy tales to accomplish its potential of helping children across their childhood.